Continuous (hydro-)dechlorination of aromatic chloride compounds in benzyltoluene - Mitländer, Kerstin; Henseler, J.; Rullo, F.; Nathrath, Phillip; Geißelbrecht, M.; Wasserscheid, Peter; Schühle, Patrick (International Journal of Hydrogen Energy, 2025)
Benzyltoluene is an attractive liquid organic hydrogen carrier (LOHC) compound but needs to be purified after its technical synthesis to remove chloride impurities that would harm the Pt-based hydrogenation and dehydrogenation catalysts used for the reversible LOHC loading and unloading with hydrogen. For this purpose the dechlorination of chlorobenzyltoluene in a benzyltoluene matrix was studied in a continuously operated trickle bed reactor using a commercially available nickel catalyst. The results indicate that the removal of chlorobenzyltoluene is mainly adsorption based. Rapid aging experiments with purposely added chloroaromatic compounds (chlorobenzene and chloronaphthalene) in quantities of up to 9000 ppm suggest that high chloroaromatic loadings lead to reduced dechlorination activity due to a rapid blocking of active sites. The dechlorination capacity per gram of the used catalyst material was determined to be in the range of 2 kg of technical benzyltoluene.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Benzyltoluene; Chloroaromatics; Chlorobenzene; Dechlorination; LOHC

Highly durable spray-coated plate catalyst for the dehydrogenation of perhydro benzyltoluene - Nathrath, Phillip; Raed Ramzi, Yousuf; Bierling, Markus; Thiele, Simon; Wasserscheid, Peter; Schühle, Patrick (Catalysis: Science and Technology, 2024)
In this study, we introduce a new spray coating technique to produce porous catalytic layers for the dehydrogenation of hydrogen carriers. The composition of the sol-gel composite dispersion is adjusted by a design of experiments (DoE) approach in order to reach excellent spraying processability, high coating stability, and a high coating load. In this way, coatings with remarkably high thicknesses of up to 500 μm, good durability, and decent adherence on stainless steel substrates were achieved. Furthermore, the precise adjustment of the coating loads and thicknesses of the highly porous γ-alumina catalyst support coating is demonstrated using the developed approach. Coating of different line-of-sight geometries, e.g., corrugated plates, is also shown. The coated plates have been impregnated with platinum and tested in the highly endothermic dehydrogenation of perhydro benzyltoluene. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) revealed an increasing penetration depth of platinum into the coating layer with higher platinum loadings. For the dehydrogenation reaction, high surface related productivities of 0.8 mgH2 min−1 cm−2 using a platinum loading of 3.7 wt% were reached, and the coatings proved completely mechanically stable under these hydrogen release conditions.
CRIS-Team Scopus Importer:2024-02-09

Hydrogen release from liquid organic hydrogen carrier using plate catalysts in continuous and dynamic operation - Nathrath, Phillip; Baier, Benjamin; Herz, N; Wituschek, Simon; Raed Ramzi, Yousuf; Merklein, Marion; Li, M.; Lederle, F.; Wasserscheid, Peter; Hübner, E.G.; Schühle, Patrick (Chemical Engineering Journal, 2025)
Significant fluctuations in energy supply are anticipated with the increasing utilization of renewable energy sources. To mitigate these fluctuations, green hydrogen released from Liquid Organic Hydrogen Carrier (LOHC) systems offers a promising solution. The use of plate catalysts in novel continuous reactor configurations enables favorable heat and mass transfer rates to drive this highly endothermic hydrogen release reaction. These catalytic plate reactors facilitate dynamic operation modes for an effective response to rapid changes in hydrogen and energy demand. In this study the performance of an established spray-coated plate catalyst is tested for the first time in continuous and dynamic operation modes. In detail, the productivity in hydrogen release from the LOHC-molecule perhydro benzyltoluene (H12-BT) is determined using a catalytic plate reactor and a tailored restart protocol was developed to maintain high hydrogen release productivities after a reactor shutdown. The plate catalysts showed good activity of up-to 0.25 mgH2 min−1 cm−2, a highly dynamic response in hydrogen release and an excellent stability under stationary and fluctuating conditions. Furthermore, a novel non-additive manufacturing method for plate catalysts through laser-texturing is introduced. The morphology of these new structures is characterized and their dehydrogenation performance is compared to the superior spray-coated benchmark.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Benzyltoluene; Dehydrogenation; Laser-texturing; LOHC; Plate reactor

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene† - Schörner, Markus; Solymosi, Thomas Andrew; Raczka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt–alumina on steel beads, b) Pt–alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with P
Keywords: Hydrogen storage; Inductive heating; LOHC; Platinum; Perhydro benzyltoluene

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene - Schörner, Markus; Solymosi, Thomas; Razcka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt-alumina on steel beads, b) Pt-alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with Pt.
CRIS-Team Scopus Importer:2024-08-23